Survey Sarana dan Prasarana Pembelajaran Pendidikan Jasmani Olahraga dan Kesehatan pada SDN Gugus Yos Sudarso Batang - rukhmawan, wahyu bagus; Supriyono, Supriyono (Indonesian Journal for Physical Education and Sport, 2023)
The purpose of this study was to determine the feasibility of learning facilities and infrastructure for physical education, sports and health at Gugus Yos Sudarso Elementary School, Batang District. This research is a survey research that is included in qualitative research with the sources of research data are school principals, PJOK teachers, and students. Methods of data collection using observation, interviews, and documentation. The data analysis of this research used the data reduction stage, the data presentation stage, the conclusion drawing stage and the validity of the data using the data credibility test by increasing persistence and triangulation. From the results of the research that has been described regarding the feasibility of PJOK facilities and infrastructure at SD Gugus Yos Sudarso, Batang Districtseen from the indicators the feasibility of learning facilities and infrastructure physical education, sports and health by adjusting learning, especially for the level and ability of elementary school students, namely: safe, easy and cheap, attractive, spurring to move, according to need, according to purpose, not easily damaged, in accordance with the environment then the facilities and infrastructure owned are categorized as suitable for use in the learning process of physical education, sports and health.